Arterial pressure variations as parameters of brain perfusion in response to central blood volume depletion and repletion - Bronzwaer, Anne-Sophie G. T.; Stok, Wim J.; Westerhof, Berend E.; van Lieshout, Johannes J. (Frontiers in Physiology, 2014)
Rationale: A critical reduction in central blood volume (CBV) is often characterized by hemodynamic instability. Restoration of a volume deficit may be established by goal-directed fluid therapy guided by respiration-related variation in systolic- and pulse pressure (SPV and PPV). Stroke volume index (SVI) serves as a surrogate end-point of a fluid challenge but tissue perfusion itself has not been addressed. Objective: To delineate the relationship between arterial pressure variations, SVI and regional brain perfusion during CBV depletion and repletion in spontaneously breathing volunteers. Methods: This study quantified in 14 healthy subjects (11 male) the effects of CBV depletion (by 30 and 70 degrees passive head-up tilt (HUT)) and a fluid challenge (by tilt back) on CBV (thoracic admittance), mean middle cerebral artery (MCA) blood flow velocity (Vmean), SVI, cardiac index (CI) , PPV and SPV. Results: PPV (103±89%, p< 0.05) and SPV (136±117%, p< 0.05) increased with progression of central hypovolemia manifested by a reduction in thoracic admittance (11±5%, p< 0.001), SVI (28±6%, p< 0.001), CI (6±8%, p< 0.001) and MCAVmean (17±7%, p< 0.05) but not in arterial pressure. The reduction in MCAVmean correlated to the fall in SVI (R2=0.52, p< 0.0001) and inversely to PPV and SPV (R2=0.46 (p< 0.0001) and R2=0.45 (p< 0.0001), respectively). PPV and SPV predicted a ≥15% reduction in MCAVmean and SVI with comparable sensitivity (67%/ 67% vs. 63%/ 68% respectively) and specificity (89%/94% vs. 89%/94%, respectively). A rapid fluid challenge by tilt-back restored all parameters to baseline values within one minute. Conclusion: In spontaneously breathing subjects, a reduction in MCAVmean was related to an increase in PPV and SPV during graded CBV depletion and repletion. Specifically, PPV and SPV predicted changes in both SVI and MCAVmean with comparable sensitivity and specificity, however the predictive value is limited in spontaneously breathing subjects.